Clinical and genetic evaluation of six children with diffuse capillary malformation and undergrowth. Issue 5 (1st July 2020) - Cubiró, Xavier; Rozas‐Muñoz, Eduardo; Castel, Pau; Roé Crespo, Esther; Garcia‐Melendo, Cristina; Puig, Lluis; Baselga, Eulalia
Abstract: Background: Diffuse capillary malformation with overgrowth (DCMO) has been well described. However, capillary malformation with undergrowth (CMU) has been less reported in the literature. Objectives: We sought to describe the clinical features and determine associated somatic mutations in patients with CMU. Methods: We searched our multidisciplinary vascular anomalies clinic database for patients with CMU. Girth and length limb measurements were performed. In case of discrepancies in length, long leg radiograph studies were obtained. Whole‐exome sequencing of blood and involved tissue DNA was carried out. Results: We included six patients with CM and soft‐tissue and bone undergrowth. CMs were patchy, reticulated, segmental, poorly demarcated, pink‐red stains affecting the lower limb (five patients) or the whole hemibody (one patient). In five patients, the stain was diffuse, affecting more than one anatomic region. Prominent superficial veins were observed in three patients. Five patients presented with lower limb girth discrepancy; in three of them, there was also lower limb length discrepancy. In the remaining patient, only lower limb length discrepancy was found. Whole‐exome sequencing from DNA tissue/blood detected previously described pathogenic somatic mutations on DDR2 (c.314G > A; p.Arg105His), GRHL2 (c.791A > G; p.Glu264Gly), and PIK3CA (c.2740G > A; p.Gly914Arg) genes. Conclusion: We propose the term "diffuse capillary malformation with undergrowth" for extensive reticular CMs associated with proportionate undergrowth. All our patients had a favorable outcome, and no genotype‐phenotype association was found.